Relation of Serum Hepcidin Levels and Restless Legs Syndrome in Patients Undergoing Peritoneal Dialysis - Guo, Yanhong; Sang, Yuan; Pu, Tian; Li, Xiaodan; Wang, Yulin; Yu, Lu; Liang, Yan; Wang, Liuwei; Liu, Peipei; Tang, Lin (Frontiers in Medicine, 2021)
Introduction: Restless legs syndrome is a common and severe complication in patients undergoing peritoneal dialysis (PD), which seriously affects the life quality and prognosis of patients undergoing PD. Unfortunately, there are still no effective prevention and treatment measures. Serum hepcidin was demonstrated to be related to primary restless legs syndrome (RLS), whereas there are no studies on the relationship between serum hepcidin and RLS in patients undergoing PD. We aimed to evaluate the role and function of serum hepcidin in patients undergoing PD with RLS. Methods: A total of 51 patients undergoing PD with RLS and 102 age-and gender-matched patients undergoing PD without RLS were included. We collected the clinical data including serum hepcidin of those patients undergoing PD. We scored the severity of RLS according to the International restless leg Syndrome Research Group rating scale (IRLS). We compared the clinical characteristics of the two groups and evaluated the determinant factors of RLS by Logistic regression analysis. In addition, we evaluated the diagnostic value of serum hepcidin in patients undergoing PD with RLS by receiver operating characteristic (ROC) curve. We also analyzed the influencing factors of IRLS by multivariate linear regression analysis. Results: The duration of PD, serum hepcidin, and calcium were found to be significantly higher in patients undergoing PD with RLS than those patients undergoing PD without RLS (P < 0.001, P < 0.001, and P = 0.002, respectively). The level of hemoglobin, albumin, and RKF were significantly lower in patients undergoing PD with RLS (P = 0.002, P = 0.042, and P < 0.001, respectively). The duration of PD [odds ratio (OR) 1.038, 95% CI: 1.017, 1.060, P < 0.001], hemoglobulin level (OR 0.969, 95% CI: 0.944, 0.995, P = 0.019), calcium level (OR 9.224, 95% CI: 1.261, 67.450, P = 0.029), albumin level (OR 0.835, 95% CI: 0.757, 0.921, P < 0.001), hepcidin level (OR 1.023, 95% CI: 1.009, 1.038, P = 0.001), and RKF (OR 0.65, 95% CI: 0.495, 0.856, P = 0.002) are independent determinant factors of RLS in patients undergoing PD. Multivariate linear regression analysis revealed that, in addition to albumin, they were also independently associated with the severity of RLS. Conclusion: A significant relation was detected between serum hepcidin level and RLS in patients undergoing PD.